Evaluasi Penggunaan Obat pada Ibu Hamil - Risna, Risna; Litaay, Gabriela Welma; Sari, Nawang Wulan Nago Pita; Imba, Farhan; Setyawan, Ferdinta Daniasta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the pattern and level of safety of drug use in pregnant women in the Working Area of ​​Health Center X, Jayapura Regency. The method used is descriptive observational research. The results of the study showed that there are groups of drugs that are most often used during pregnancy are iron tablets (100%), vitamins (85.71%), Calcium (77.14%), Folic Acid (65.71%), and nausea and vomiting drugs (34.28%). In terms of the level of safety of the drugs used, there are 3 types of medications with category C (15%) and 7 types of drugs that have not been categorized 35%. In conclusion, drugs used during pregnancy, both with a doctor's prescription and self-medication, are generally safe. Still, there are several drugs and supplements whose safety category is C and unknown (N) according to the FDA. Keywords: FDA, Pregnant Women, Drugs, Self-Medication